ANALISIS TINGKAT BRAND LOYALTY PRODUK MIE INSTAN MEREK INDOMIE DI KOTA PEKANBARU - Sutrisna, Muhammad Dede; Jusherm, Jusherm; Musfar, Tengku Firli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to measure the level of consumer loyalty, switcher buyer, habitual buyer, satisfied buyer, likes the brand, and committed buyer. The population in this study is the people who make purchases of Indomie in Pekanbaru, with a sample of 140 respondents obtained by purposive sampling technique. Data analysis techniques used in this study using descriptive analysis and cumulative percentage.From the results of descriptive analysis in percentage are: (1) switcher buyer have value equal to 36,9%, (2) habitual buyer has value equal to 69,3%, (3) satisfied buyer have value equal to 80%, (4) likes the brand which has a value of 88.6%, (5) committed buyers have a value of 71%. Most consumers are at likes the brand level of 88.6%, while the pyramid arrangement of brand loyalty is an inverse triangle shape. This includes that the Indomie brand has strong brand equity.Keywords: Brand Loyalty, switcher, habitual buyer, satisfied buyer, liking of the brand, committed buyer.